Parliamentary scrutiny of the EU’s Common foreign and security policy - Herbel, Annika (West European politics, 2016)
This paper analyses under what conditions parties engage in parliamentary scrutiny of the European Union’s Common Foreign and Security Policy. With insights from comparative literature on parliamentary oversight, two main incentives are identified. On the one hand, opposition parties initiate scrutiny to reduce their information asymmetry vis-à-vis the government; on the other hand, coalition parties use parliamentary scrutiny to control their partners. Empirically, the article uses information on scrutiny activities in six EU member states (Germany, France, Italy, Poland, Slovakia, United Kingdom) covering 13 years and 21 governments. The findings suggest that opposition parties scrutinise the government if they have access to strong oversight instruments. In contrast, the strength of oversight instruments is not important for coalition partners. They resort to means of scrutiny if the leading minister is weak. Coalitions with a greater number of parties engage in scrutiny less often. Moreover, scrutiny is especially observed in questions with more direct distributional consequences (‘intermestic’ issues).